ChemInform Abstract: Enantioselective Rh(I)‐Catalyzed Addition of Arylboronic Acids to Cyclic Ketimines. Issue 14 (March 2016) - Kong, Jongrock; McLaughlin, Mark; Belyk, Kevin; Mondschein, Ryan
Abstract: In the presence of the chiral ligand SL‐W001‐1 (Walphos), various target compounds bearing a tertiary stereocenter are obtained with excellent enantioselectivity.